The influence of principals’ managerial and school committee participation on the quality of education at elementary schools - Djafri Achmad; Yasir Arafat; Mulyadi Mulyadi (Indonesian Institute for Counseling, Education and Therapy (IICET), 2021)
This study aimed to investigate: (1) the influence of principals’ managerial on the quality of education; (2) the influence of committee participation on the quality of education; and (3) the influence of the principals’ managerial and committee participation simultaneously on the quality of education. The data in this study were collected through distributing questionnaires to respondents. Them they were analyzed by using multiple regression analysis through t test, F test, and determination coefficient test. The population in this study were all teachers at Elementary Schools of Babat Supat District which consisted of 294 teachers. The sampling technique used in this study was probability sampling with a sample size of 75 people. The results of the study showed that: (1) principals’ managerial individually influences the quality of education at Elementary Schools of Babat Supat District; (2) participation of school committee individually influences the quality of education at Elementary Schools of Babat Supat District; (3) principals’ managerial and school committee participation simultaneously influence the quality of education at Elementary Schools of Babat Supat District.